2019
DOI: 10.1108/jfbm-09-2018-0049
|View full text |Cite
|
Sign up to set email alerts
|

Principles for innovation management in family firms

Abstract: Purpose Family firms (FF) reveal a considerable heterogeneity in their innovation behavior. Due to the successful long-term preservation of their innovation capacity via special resources and routines, multi-generational FF are of special interest in terms of learning from good practices. Against this background, the purpose of this paper is to ascertain principles for successful innovation behavior in long-term successful FF and to contribute to bridging the theory-practice gap. Design/method/approach Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 90 publications
0
17
0
Order By: Relevance
“…Dwelling on the subject of socio-emotional wealth and its restrictive influence on family firms' innovation activity, Calabro et al ( 2019) indicate that family business owners consider big innovation projects as threats to capital and family control. Equally, Frank et al (2019) correspond that family firms' sense of independence hinders their openness to external collaboration and innovation opportunities, which consequently slows down new product and process development. Yet, Calabro et al ( 2019) also suggest that conflict within the family and different risk-taking approaches tend to engender agency costs that would eventually limit availability of resources for commitment to innovation projects.…”
Section: Strategic Commitment To Environmental Issues and Family Firm...mentioning
confidence: 99%
“…Dwelling on the subject of socio-emotional wealth and its restrictive influence on family firms' innovation activity, Calabro et al ( 2019) indicate that family business owners consider big innovation projects as threats to capital and family control. Equally, Frank et al (2019) correspond that family firms' sense of independence hinders their openness to external collaboration and innovation opportunities, which consequently slows down new product and process development. Yet, Calabro et al ( 2019) also suggest that conflict within the family and different risk-taking approaches tend to engender agency costs that would eventually limit availability of resources for commitment to innovation projects.…”
Section: Strategic Commitment To Environmental Issues and Family Firm...mentioning
confidence: 99%
“…Recent conceptual study (Calabrò et al , 2019) has demonstrated the significance of innovativeness for family firms, and the relationship between family firms and innovativeness has been addressed by only a few studies (Frank et al , 2019). This research therefore enhances our knowledge in the domain of family firm innovation.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is evidence that some trust-breaching practices, such as asymmetry in the accountability of incentive norms impair the innovation of family firms (De Massis et al, 2016). A study about innovative successful practices of family enterprises identified trust and constructive conflict as mutually reinforced processes in the innovation process (Frank et al, 2019).…”
Section: Trustmentioning
confidence: 99%
“…Trust in the family firm's collective abilities also increases innovation (Holt and Daspit, 2015 ). Indeed, trust relationships with the external stakeholders also contribute to innovation by promoting honest feedback in evaluating innovation projects (Frank et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%